The Political Economy of Climate Change Mitigation in Argentina, Brazil and Peru - Larissa Basso (Iberoamericana: Nordic Journal of Latin American and Caribbean Studies)
Climate change is caused by rising concentration of Greenhouse Gases (GHG) in the atmosphere, so mitigating it requires reducing GHG emissions. For most countries, energy is the major source of emissions, so energy transition is the most effective mitigation policy. In Latin America, however, the picture is more nuanced since emissions from land use, land use change and forestry (LULUCF) also play a key role. This is due to Latin American economies’ profile and position in global value chains as exporters of primary commodities. In this paper, by employing thick description methodology and using the lenses of historical institutionalism and political economy, we offer a preliminary analysis of how coalitions formed around LULUCF issues, especially deforestation, in Argentina, Brazil and Peru influence the institutions that define and regulate the political struggle on the topic and frame climate action in each of the countries.